Notas Poéticas Corporales (2022)
This writing is part of a reflective study on emotions and their place in the body, It is divided into two parts, where the first summarizes the basic concepts of the project such as the site of emotions, their impact on the body, their origin and synthesizes a theoretical study on emotional conditions on health and life usually. The second part contains anecdotal descriptions of the plastic processes that were given thanks to the curiosities about the emotions in the body, the affectivity, the vulnerability, the construction of individuals, time and their subsequent development in the work Body Poetic Notes. This segment linearly narrates the process and discoveries that occurred in the middle of the elaboration and exhibition of part of the work.